CAXII inhibitors: Potential sensitizers for immune checkpoint inhibitors in HCC treatment - Han, Rui; Li, Jiayin; Hony, Jing; Xiao, Zhiwei; wang, Jinghui; Yao, Man; Liang, Shufang; Lu, Lingeng (Frontiers in Immunology, 2023)
Hepatocellular carcinoma (HCC) is a lethal malignancy with the lack of effective treatments particularly for the disease at advanced stage. Even though immune checkpoint inhibitors (ICIs) have made a great progress in the treatment of HCC, durable and ideal clinical benefits still cannot be achieved in a plenty of patients with HCC. Therefore, novel and refined combinations of ICIs are needed for enhancing the therapeutic effect. The latest study has reported that CAXII inhibitor (CAXIIi), as a novel type of anticancer drug, can modify immunosuppression by affecting hypoxic/acidic metabolism, and altering the functions of monocytes and macrophages by regulating the expression of CCL8. These observations shine a light on improving PD-1/PD-L1 immunotherapy in combination with CAXII inhibitors. This mini-review aims to ignite enthusiasm to explore the application of CAXIIis in combination with immunotherapy for HCC.